BIM and Future of Quantity Surveyors in Malaysia’s Construction Industry - Chan, Wai Bin; Farhana, Mohd Zaini; Nurulhuda, Ahamad; Sangeetha, Arjinan; Zetty, Pakir Mastan (INTI International University, 2020)
Over the past era, the complicated procedures and complexity of designs had become challenging to the Quantity Surveying practices. Errors in term of quantities and time consumption are the major impact on Quantity Surveyors when it comes to performing their task. Building Information Modelling (BIM) has been introduced in 2012, developed and expanded in the construction industry to minimize errors while improving the efficiency of work in terms of time, cost, and accuracy of quantities measured. Thus, this research aims to identify the impact of BIM tools on the roles currently played by the Quantity Surveyors in our local industry. To achieve the aim, this research investigated the usage of BIM tools by the Quantity Surveying consultant firms by analysing the demand for its usage and its effect to the overall profession. A survey-based approach was conducted, whereby 33 sets of sampling size were identified through a random sampling method with only 25 sets of questionnaires received from the respondents. Findings from questionnaires showed that the adoption of BIM did leave significant impacts on Quantity Surveyors practices in the long run. Results have shown that the level of awareness on BIM is still low among the Quantity Surveyors. However, BIM is still worth being implemented as it could help to improve in terms of time saving and accuracy of measurement. This will improve the Quantity Surveyors' profession tremendously in the future